2013
DOI: 10.1161/hypertensionaha.111.00647
|View full text |Cite
|
Sign up to set email alerts
|

Novel Regulation of Cardiac Metabolism and Homeostasis by the Adrenomedullin-Receptor Activity-Modifying Protein 2 System

Abstract: Abstract-Adrenomedullin (AM) was identified as a vasodilating and hypotensive peptide mainly produced by the cardiovascular system. The AM receptor calcitonin receptor-like receptor associates with receptor activity-modifying protein (RAMP), one of the subtypes of regulatory proteins. Among knockout mice ( −/− ) of RAMPs, only RAMP2 −/− is embryonically lethal with cardiovascular abnormalities that are the same as AM −/− . This suggests that the AM-RAMP2 system is particularly important for the cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Interestingly, a recently published study demonstrated that a cardiomyocyte-specific Ramp2 deletion led to a DCM-like phenotype due to mitochondrial dysfunction and irregular calcium handling, which the authors attribute to loss of CLR/AM signaling. 46 Similarly, this study suggests that cardiomyocyte loss of Ramp2 in the Ramp2 −/− Tg mice is likely responsible for the DCM. Moreover, our data demonstrates that neither cardiomyocyte- or vSMC-specific loss of Calcrl during development or conditional Calcrl deletion in adults recapitulate the DCM phenotype observed in the Ramp2 −/− Tg and the aforementioned Ramp2 flox/flox ; α MHC-MerCreMer mice.…”
Section: Discussionsupporting
confidence: 58%
“…Interestingly, a recently published study demonstrated that a cardiomyocyte-specific Ramp2 deletion led to a DCM-like phenotype due to mitochondrial dysfunction and irregular calcium handling, which the authors attribute to loss of CLR/AM signaling. 46 Similarly, this study suggests that cardiomyocyte loss of Ramp2 in the Ramp2 −/− Tg mice is likely responsible for the DCM. Moreover, our data demonstrates that neither cardiomyocyte- or vSMC-specific loss of Calcrl during development or conditional Calcrl deletion in adults recapitulate the DCM phenotype observed in the Ramp2 −/− Tg and the aforementioned Ramp2 flox/flox ; α MHC-MerCreMer mice.…”
Section: Discussionsupporting
confidence: 58%
“…37,38) PPARα and ERRα are downstream factors of PGC-1α and mainly regulate mitochondrial lipid metabolism (by PPARα), the TCA cycle, and the electron transport chain (by ERRα). 39) In addition, recent studies show that AM regulates mitochondria via cAMP-cAMP response element binding protein (CREB)-PGC-1 pathway in mice, 22,40) and has an antiapoptotic effect against DOX via cAMP-dependent pathway in cultured cardiac myocytes. 30) These results suggest that exogenous AM administration is able to protect the heart via regulation and protection of cardiac mitochondria in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…17) In addition, AM has several functions, including antioxidative, 18,19) anti-inflammatory, 20) and angiogenic effects, 21) as well as acting as a regulator of mitochondrial function. 22) In AM gene knockout (AM KO) mice, homozygotes died in utero with abnormal cardiovascular development, and heterozygotes showed elevated blood pressure. 23) Cardiac hypertrophy and fibrosis were observed in AM KO heterozygotes when subjected to cardiovascular stress.…”
mentioning
confidence: 99%
“…The critical intracellular second messenger, cAMP, regulates numerous growth and developmental processes in the myocardial cell, including discrete compartments to maintain homeostasis and simultaneously control diverse cellular functions (23). Compared with sham-operated group, the cAMP level in the H-HF rats was decreased.…”
Section: Discussionmentioning
confidence: 99%